2022
DOI: 10.1017/s1092852922001109
|View full text |Cite
|
Sign up to set email alerts
|

Compulsive buying behavior and its association with emotional distress, depression, and impulsivity in general population: an online survey

Abstract: Background Compulsive buying behavior or pathological buying is increasingly being recognized as a psychiatric disorder, and various psychosocial factors have been proposed to contribute to this problem. This study aimed to identify the association between compulsive buying behavior, stress, anxiety, depression, and impulsivity. Methods This cross-sectional, online survey used Google Forms to collect sociodemographic and clinical details of the participants between June 2021 and August 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The US Bureau of Labor Statistics shows that the time spent by persons aged 15 years and over purchasing goods and services was 40.8 min/day in 2021 [1]. Even though this time is decreasing compared with the pre-pandemic period (45 min/day in 2019) and because of the growth of online shopping, people often go shopping not just to acquire stuff but also to alleviate emotional distress [2,3]. In Australia, a survey conducted from November 2020 to July 2021 showed that males shopped for 60 min/day while females shopped for 66 min [4].…”
Section: Introductionmentioning
confidence: 99%
“…The US Bureau of Labor Statistics shows that the time spent by persons aged 15 years and over purchasing goods and services was 40.8 min/day in 2021 [1]. Even though this time is decreasing compared with the pre-pandemic period (45 min/day in 2019) and because of the growth of online shopping, people often go shopping not just to acquire stuff but also to alleviate emotional distress [2,3]. In Australia, a survey conducted from November 2020 to July 2021 showed that males shopped for 60 min/day while females shopped for 66 min [4].…”
Section: Introductionmentioning
confidence: 99%